Investigation on rational width of coal pillar and roadway support in isolated panel of extra-thick coal seam - He, Xiang; He, Shuxin; Cai, Yongbo; Xu, Ruiyang; Yang, Ke (Frontiers in Earth Science, 2023)
Abstract: This paper used numerical simulation and field measurement methods to study reasonable width of coal pillar and roadway support in isolated panel of extra-thick coal seam. Numerical modeling shows that the peak value of vertical stress in isolated panel reaches 32.9 MPa, and the stress concentration factor is 2.99, which is more affected by the mining of adjacent panel, and the peak stress on both sides is higher. By comparing the variation characteristics of stress and displacement with different pillar widths, it is shown that the 6 m wide pillar can meet the load requirements of overlying strata and ensure that the roadway is in a good stress environment. Based on the asymmetry of surrounding rock deformation, the final joint control technology of asymmetric anchor cable truss, high-strength anchor cable, and coal pillar grouting is proposed and get good control effect on site. The research results provide guidance value for surrounding rock control under similar geological conditions.